2020
DOI: 10.1002/lary.28695
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Vestibular Schwannoma Growth Using a Two‐Dimensional U‐Net Convolutional Neural Network

Abstract: Objectives/Hypothesis To determine if an automated vestibular schwannoma (VS) segmentation model has comparable performance to using the greatest linear dimension to detect growth. Study Design Case‐control Study. Methods Patients were selected from an internal database who had an initial gadolinium‐enhanced T1‐weighted magnetic resonance imaging scan and a follow‐up scan captured at least 5 months later. Two observers manually segmented the VS to compute volumes, and one observer's segmentations were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Similarly, only four manuscripts reported interrater variability. The most frequently used metric for interrater variability, the dice coefficient, was between 0.89 and 0.94 [ 5 , 112 , 114 , 115 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, only four manuscripts reported interrater variability. The most frequently used metric for interrater variability, the dice coefficient, was between 0.89 and 0.94 [ 5 , 112 , 114 , 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…George-Jones et al analyzed a cohort of 65 patients with a median tumor volume of only 0.28 mL [ 114 ]. Unlike other publications, the authors did not report dice coefficients, but instead tried to analyze how well the model was able to detect growth compared to the manual segmentations which were used as the ground truth.…”
Section: Resultsmentioning
confidence: 99%
“…George-Jones et al (13) demonstrated the use of an automated segmentation model to detect growth in vestibular schwannomas on GdT1WI. A direct comparison in segmentation performance with our model cannot be made because George-Jones et al did not report performance metrics such as the Dice score for the model itself, instead focusing on the ability of the model to detect tumor growth in comparison to manual segmentation using the greatest linear dimension.…”
Section: Discussionmentioning
confidence: 99%
“…One publication used an NN to predict vs. recurrence following surgery from clinical parameters in tabular format [23]. The remaining four publications used NNs to segment VS for either radiotherapy planning or response assessment [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%